The Effect of Calendarized Drug Package on Patients Compliance with Antibiotics - Zulfa, Ilil Maidatuz; Handayani, Widya (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Patients’ compliance with antibiotics has been one of the global challenges in combating antibiotics resistance. Patients will tend to forget their antibiotics, especially when they feel better. Related to this phenomenon, the development of medication reminder media is essential. AIM: This experimental study was aimed to develop and apply calendarized package as a medication reminder media in patients with short-course antibiotics to improve their compliance. METHODS: Calendarized package was prepared from the labeling of the original package of antibiotics with stickers. Patients above 18 years old who were prescribed short-course oral antibiotics (not more than 7 days) during the study period were asked to participate in this study. Patients were grouped into two groups (control and intervention group). Patients’ demographical data, medications prescribed, and the last antibiotics course day was recorded. Patients were then contacted for compliance evaluation on the latest antibiotics course day. RESULTS: A total of 150 patients who met the inclusion criteria were recruited in this study. Seventy-six patients were grouped into the intervention group, while the remaining 74 patients were the control group. The results showed that the number of compliant patients in the intervention group was higher (72.37%) than those in the control group (45.95%), respectively (p < 0.000). CONCLUSION: The application of the calendar on the package indicates the positive impact on the patients’ compliance with antibiotics. However, in this study, the compliance measurement was conducted indirectly because of the coronavirus disease 2019 pandemic. However, several limitations should be considered. Future research using a bigger sample size and stricter compliance measurement method is needed to confirm this finding.